Development of geographic information systems for Small and Medium Enterprise centres. Issue 3 (March 2021) - Satria, E; Cahyana, R; Bachtiar, Y; Fatimah, D D S
Abstract: The small and medium enterprises (SME) actors support the economic development in Indonesia. The number of SMEs is increasing rapidly every year. One obstacle faced by SME is the difficulty of consumers to get business information and find the location of the place of business. The aim of this research is to design and to develop a geographic information system regarding the mapping of business centres. The system developed provides information in the form of a visual display of the business profile and business location of the SME. The method used is the Rational Unified Process, which consists of inception, elaboration, construction and transition. The results of the study consisted of the design and prototype of the geographic information system of the SME business centre that made it easy for users to find location information and SME business profiles. The business centre searches feature displays business locations in the form of a map that is connected with google map technology. In addition, the system built displays the latest and most accessible information as well as the SME contact information of search results. For system users who are interested in becoming members of the business centre, registration features are provided so that they get the facilities provided by the business centre. Future studies are expected to be able to show the route of travel from the user's position to the business centre by considering the closest distance or based on criteria determined by the user.